2016
DOI: 10.1016/j.tibs.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Impact on Histone Acetylation and Transcription in Ageing

Abstract: Loss of cellular homeostasis during aging results in altered tissue functions and leads to a general decline in fitness and, ultimately, death. As animals age, the control of gene expression, which is orchestrated by multiple epigenetic factors, degenerates. In parallel, metabolic activity and mitochondrial protein acetylation levels also change. These two hallmarks of aging are effectively linked through the accumulating evidence that histone acetylation patterns are susceptible to alterations in key metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 128 publications
6
115
0
2
Order By: Relevance
“…It is becoming evident that histone acetylation plays a more nuanced role in gene regulation, with site specific changes in histone acetylation playing just as important a role as more global alterations (Peleg et al, 2016). It is notable that lifespan increases associated with treatment with histone deacetylase inhibitors (HDACi's) such as trichostatin A (TSA) and butyrate often show more targeted gene-specific effects (Tao et al, 2004;Walsh et al, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is becoming evident that histone acetylation plays a more nuanced role in gene regulation, with site specific changes in histone acetylation playing just as important a role as more global alterations (Peleg et al, 2016). It is notable that lifespan increases associated with treatment with histone deacetylase inhibitors (HDACi's) such as trichostatin A (TSA) and butyrate often show more targeted gene-specific effects (Tao et al, 2004;Walsh et al, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Such disturbance may lead to human diseases, including cancer, 28 inflammatory diseases, 29 Huntington’s disease, 30 and aging-associated diseases. 31 …”
mentioning
confidence: 99%
“…The close connection between metabolism and epigenetic processes was also illustrated in a study presented by Axel Imhof (LudwigMaximilians University), who showed that the attenuation of an age-dependent increase in lysine acetylation results in lifespan extension in fruit flies 12 .…”
Section: Competing Financial Interestsmentioning
confidence: 84%